Peran Posyandu Dalam Meningkatkan Kualitas Kesehatan Warga Masyarakat Di Kelurahan Uritetu Kota Ambon: Studi Kasus Di Pulugangsa - David Octovianus Roos (HIPOTESA - Jurnal Ilmu-Ilmu Sosial, 2026)
Posyandu can also be said to be part of national development to achieve small, happy and prosperous families, which in principle is carried out by families together with the community under the guidance of health workers from the local Community Health Center. The well-being of a society is a reflection of its quality of life. Quality of life itself is often divided into two categories: physical and non-physical. The Posyandu is a program includes 5 tables, namely registration, weighing, counseling, PMT, and treatment. Thus, Posyandu is an effort to fulfill basic health needs and improve the nutritional status of the community